CFTR targeted therapies: recent advances in cystic fibrosis and possibilities in other diseases of the airways. (17th June 2020) - Patel, Sheylan D.; Bono, Taylor R.; Rowe, Steven M.; Solomon, George M.
Cystic fibrosis transmembrane conductance regulator (CFTR) is an ion transporter that regulates mucus hydration, viscosity and acidity of the airway epithelial surface. Genetic defects in CFTR impair regulation of mucus homeostasis, causing severe defects of mucociliary clearance as seen in cystic fibrosis. Recent work has established that CFTR dysfunction can be acquired in chronic obstructive pulmonary disease (COPD) and may also contribute to other diseases that share clinical features of cystic fibrosis, such as asthma, allergic bronchopulmonary aspergillosis and bronchiectasis. Protean causes of CFTR dysfunction have been identified including cigarette smoke exposure, toxic metals and downstream effects of neutrophil activation pathways. Recently, CFTR modulators, small molecule agents that potentiate CFTR or restore diminished protein levels at the cell surface, have been successfully developed for various CFTR gene defects, prompting interest in their use to treat diseases of acquired dysfunction. The spectrum of CFTR dysfunction, strategies for CFTR modulation, and candidate diseases for CFTR modulation beyond cystic fibrosis will be reviewed in this manuscript. CFTR dysfunction may be part of the pathophysiology of many diseases of the airways. Exploration of mechanisms of dysfunction and options for CFTR-directed therapies are examined in this article .http://bit.ly/33o6nDu